2020
DOI: 10.1101/2020.04.17.046409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First-generation EGFR-TKI plus chemotherapy versus EGFR-TKI alone as first-line treatment in advanced NSCLC with EGFR activating mutation: a systematic review and meta-analysis of randomized controlled trials

Abstract: The aim of this meta-analysis was to evaluate efficacy and toxicity of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) in combination with chemotherapy (CT) compared to EGFR-TKI monotherapy as first-line treatment in advanced non-small cell lung cancer (NSCLC) harboring activating EGFR mutation.A systematic literature search of randomized controlled trials using Cochrane Library, PubMed, Embase, and Web of Science, was performed up to Jan. 7 th , 2020. A total of eight randomized trials i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The meta-analyze may support these results, showing that TKIs plus chemotherapy, the first-line therapy, significantly increase ORR while improving OS and DFS for advanced NSCLC cases with EGFR mutation. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analyze may support these results, showing that TKIs plus chemotherapy, the first-line therapy, significantly increase ORR while improving OS and DFS for advanced NSCLC cases with EGFR mutation. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analyze may support these results, showing that TKIs plus chemotherapy, the first-line therapy, significantly increase ORR while improving OS and DFS for advanced NSCLC cases with EGFR mutation. [18] EGFR-TKIs have been recommended as first-line therapies for patients with EGFR-mutant NSCLC, and patients tend to benefit from adjuvant EGFR-TKI treatment in terms of DFS and OS. The ability of adjuvant EGFR-TKI treatment, however, remains unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients develop drug resistance at around 9-14 months after administration of first-line treatment with firstor second-generation EGFR-TKIs. The most common mechanisms for acquired drug resistance include secondary point mutations (e.g., T790M mutation), bypass activation (e.g., c-MET amplification), human epidermal growth factor receptor 2 (HER2) mutation, and histological type transformation (2,3). The T790M mutation is the most common mechanism for acquired drug resistance (4), occurring in around 60% of cases.…”
Section: Case Reportmentioning
confidence: 99%
“…The TAKUMI trial randomised sixty-two patients who had developed T790M resistance mutation after first line EGFR-TKI therapy to either osimertinib with combination carboplatin-pemetrexed versus osimertinib alone and found that there was no significance difference in median PFS (35). In regards to safety, a metaanalysis of combination chemotherapy with first-generation TKIs found overall increased toxicities most notably myelosuppression and gastrointestinal side effects (36). As well, no specific pattern of toxicity leading to dose modification or discontinuation was observed, although one patient discontinued study treatments due to pneumonitis (37).…”
Section: Trials Intensifying Tki Regimensmentioning
confidence: 99%